Contact and Noncontact Ultrasonic Nondestructive Test in Reinforced Concrete Beam - Jason Maximino C. Ongpeng; Andres Winston C. Oreta; Sohichi Hirose (Advances in Civil Engineering)
Contact-type ultrasonic test is commonly used in construction industry where gel-couplant is applied to the material being tested and the transducers to assure that wave propagation will travel through without any air gaps. However, this method has disadvantages, since surface preparation is considered prior to testing. Another method of testing without the worry of air gaps that causes scattering of waves before it reaches the medium is the use of the noncontact ultrasonic test. In particular, the air-coupled ultrasonic test is done in this paper for reinforced concrete beams. Sixteen plain concrete cube specimens under the compression test and six reinforced concrete beam specimens under the four-point bending test are made with water-cement ratio of 40% and 60%. The plain concrete cubes are investigated to establish the relationship of the contact ultrasonic test and load. Added parameters are considered to investigate the sensitivity of the contact and noncontact ultrasonic test in reinforced concrete beams. These are ultrasonic wave path and the neutral axis index. It shows that the higher water-cement ratio produces good sensitivity in the noncontact ultrasonic test, since it produces more cracks on the tension face. Lower water-cement ratio gives good sensitivity with load for the contact ultrasonic test, since it has its ultrasonic wave path passing through the concrete experiencing compression. In addition, the neutral axis index for a member subjected to bending is an important factor in assessing the sensitivity of both contact and noncontact ultrasonic test.